Collectibles depicting marine life - Mumbai Archive Project Team (Jio Institute, 2024)
The drawing room is decorated with collectible items related to life at sea. Saraswati's brother, Om Prakash Nakhva, who worked as a marine engineer at the Colaba docks, acquired these items through customs office auctions.